2020
DOI: 10.1007/s11739-020-02462-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum sodium variability and acute kidney injury: a retrospective observational cohort study on a hospitalized population

Abstract: Aim of our study was to analyze the association between serum sodium (Na) variability and acute kidney injury (AKI) development. We performed a retrospective observational cohort study on the inpatient population admitted to Fondazione Policlinico Universitario A. Gemelli IRCCS between January 1, 2010 and December 31, 2014 with inclusion of adult patients with ≥ 2 Na and ≥ 2 serum creatinine measurements. We included only patients with ≥ 2 Na measurements before AKI development. The outcome of interest was AKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…4) The feature sodium may also become an important parameter for the prediction according to its high weight in the prediction, which is consistent with Lombardi's research results (44). The change in sodium level leads to a change of osmotic pressure and AKI may develop finally.…”
Section: Impact Weight Analysissupporting
confidence: 82%
“…4) The feature sodium may also become an important parameter for the prediction according to its high weight in the prediction, which is consistent with Lombardi's research results (44). The change in sodium level leads to a change of osmotic pressure and AKI may develop finally.…”
Section: Impact Weight Analysissupporting
confidence: 82%
“…Thus, the level of these ions and particles above mentioned may reflect and affect patient renal function. Sodium imbalance was generally associated with patient poor outcomes including the development of AKI, and previous studies had proved this finding (27,28). Relevant studies also found that early treatment for hyperkalemia could reduce potassium level and AKI, and potassium level was closely related to patient renal function (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 96%
“…It is a common and severe complication in hospitalized populations. The reported incidence is quite varied especially since it is strongly influenced by definition and study population with an incidence ranging from 7 to 57% [2][3][4][5][6] and with a significant burden on patient morbidity and mortality [7][8][9]. As reported by clinical and epidemiological studies, several diseases [10][11][12][13][14] show a defined seasonal variation.…”
Section: Introductionmentioning
confidence: 99%